2008
DOI: 10.1111/j.1460-9568.2008.06193.x
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling neural structures for processing of high‐ and low‐speed visual motion

Abstract: Human psychophysical and electrophysiological evidence suggests at least two separate visual motion pathways, one tuned to a lower and one tuned to a broader and partly overlapping range of higher speeds. It remains unclear whether these two different channels are represented by different cortical areas or by sub-populations within a single area. We recorded evoked potentials at 59 scalp locations to the onset of a slow (3.5 degrees /s) and fast (32 degrees /s) moving test pattern, preceded by either a slow or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 48 publications
1
17
1
Order By: Relevance
“…Indeed, a smaller mean amplitude of N1 early frontal (Bailey et al ., ) and a greater amplitude of the N1 occipital were found when threatening stimuli were presented. Likewise, the results on the N1 parietal are consistent with previous evidence (Lorteije et al ., ), with the component increasing in amplitude for faster stimuli.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Indeed, a smaller mean amplitude of N1 early frontal (Bailey et al ., ) and a greater amplitude of the N1 occipital were found when threatening stimuli were presented. Likewise, the results on the N1 parietal are consistent with previous evidence (Lorteije et al ., ), with the component increasing in amplitude for faster stimuli.…”
Section: Discussionmentioning
confidence: 88%
“…In the literature, three different N1 components have been found – an early frontal component and two late components, one that peaks across the parietal recording sites and another that peaks across the occipital recording sites (Luck, ). Given that the N1 seems to be influenced by several characteristics of the stimulus, including colour (Anllo‐Vento & Hillyard, ), location (Martinez et al ., ), perceived motion (Lorteije et al ., ) and emotional content (Carretié et al ., ; Foti et al ., ; Hart et al ., ), and given that we were interested in both the influence of the emotional, as well as the temporal, characteristics of the stimuli, all the different components of N1 were analysed. The N1 early component was evaluated as the activity at the frontal recording sites (F7, F3, FZ, F4, F8) between 110 and 135 ms (Hart et al ., ) after stimulus onset.…”
Section: Methodsmentioning
confidence: 99%
“…This is because the stimuli in the present study used low velocities compared with the velocities in actual situations, although a similar time scale was used. A previous study reported that ERPs modulated depending on high-and low-speed visual target motion because of activation of a different cortical area (e.g., Lorteije, van Wezel, & van der Smagt, 2008). Further investigation is needed to fully understand the neural mechanisms involved in movement correction of interceptive action in fast-ball sports, especially in expert players.…”
Section: Discussionmentioning
confidence: 95%
“…This would include speed and direction, and possibly even acceleration and rate of direction change. This information could be extracted, for example, from neurons in the MT area that code direction and speed (Lorteije, van Wezel, & van der Smagt, 2008). However, there may be limits on the amount of information that can be stored, such that when more targets are tracked, less information about each target is available.…”
Section: Discussionmentioning
confidence: 99%